FACTORS AFFECTING THE SALES PERFORMANCE OF PT SKP (A CASE STUDY OF SALES FORCE OF MOORLIFE INDONESIA IN JABODETABEK) - Djoni, Djoni; Oktaviani, Rina; Kirbrandoko, Kirbrandoko (Indonesian Journal of Business and Entrepreneurship, 2016)
This study discusses the factors that affect the performance of sales in the direct selling business in PT Srirara Kanaka Pratama (PT SKP). Direct selling is part of a growing sector of small and medium businesses, especially in creating alternative jobs. The purpose of this study was to identify and analyze the main factors that affect the performance of sales in PT SKP in Jabodetabek area and formulate its managerial implications. This study used a descriptive analysis to look at the characteristics of the respondent and a multiple linear regression analysis to identify factors that affect the sales performance in PT SKP. The number of respondents in this study is 60 active members. The study results showed that the factors affecting the sales performance in PT SKP are incentives and rewards from sold products. For the managerial implementation in order to improve the sales performance of its members, PT SKP will provide more interesting incentives or bonuses and increase the number of members who receive bonuses as well as the amount of bonuses by creating programs and activities supporting such a condition. It will also create more attractive products of higher selling power as a reward to increase the motivation of members in order to increase sales. Keywords: direct selling, sales performance, multiple linear regression, PT SKP